Solution of sensing failure problem: an improved two-stage detector. (8th November 2017) - Kanti, Jyotshana; Tomar, Geetam Singh
Abstract: In this paper, an improved-two-stage detection (improved-TSD) technique for spectrum sensing (SS) has been proposed. In improved-TSD technique, there are two stages, the first stage has two detectors, i.e. energy detector using a single adaptive threshold (ED_SAT) and energy detector using two adaptive thresholds (ED_TAT), organized in a parallel way, and the second stage carries decision device ( DD ) who decide the final decision using OR -rule. Graphical results confirm that proposed improved-TSD technique improves detection performance and outperforms the energy detection technique for adaptive spectrum sensing-2015 (EDT-ASS-2015) and conventional-ED (C-ED) SS techniques by 10.4 % and 31.3 % at –10 dB signal-to-noise ratio (SNR) respectively. Further, in terms of sensing time, the presented scheme performs well as compared to EDT-ASS-2015 SS scheme i.e. takes 0.5 ms sensing time at –20 dB SNR.